A Cross-Country Comparison of Reasons for Condom Use during Menses: Associations with Age and Gender Inequality. Issue 2 (2nd April 2020) - Graham, Cynthia A.; Crosby, Richard A.; Sanders, Stephanie A.; Vitzthum, Virginia J.; Milhausen, Robin R.; Yarber, William L.
Abstract: Objectives : Despite evidence that menstrual bleeding is a risk factor for sexually transmissible infections, few studies have assessed the prevalence of, and reasons for, condom use during menses. The objectives of the present study were to examine (1) the prevalence of condom use during menses; (2) if condom use during menses varies depending on age and gender inequality of country of residence; and (3) whether age and gender inequality of country of residence interact with reasons for using, and not using, condoms during menses. Methods : A sample of 25, 955 individuals from 146 countries, all reporting penile-vaginal intercourse in the past 3 months, was used. Condom use during menses over the previous 3 months, whether this varied by age and level of gender inequality in countries, and reasons for using and not using condoms during menses were assessed via a web-based questionnaire. Results : Age and gender inequality of country of residence were significant predictors of condom use during menses, with those in the younger, high gender-equality group significantly the most likely, and those in the older, low gender-equality group, the least likely to use condoms during bleeding. The three most reported reasons were "for contraception, " "I use condoms even when I don't have my period, " and "protecting your partner from your blood." Reported reasons for using and not using condoms during menses showed significant associations with age and with level of gender inequality. Conclusion : Findings highlight that globally sexually transmitted infection/HIV education programs need to promote consistent condom use across the menstrual cycle.